Early Corneal Cellular and Nerve Fiber Pathology in Young Patients With Type 1 Diabetes Mellitus Identified Using Corneal Confocal Microscopy - Szalai, Eszter; Deák, Eszter; Módis, László; Németh, Gábor; Berta, András; Nagy, Annamária; Felszeghy, Eniko; Káposzta, Rita; Malik, Rayaz A.; Csutak, Adrienne (Investigative ophthalmology & visual science, 2016)
The aim of this study was to quantify epithelial, stromal, and endothelial cell density, and subbasal nerve morphology in young patients with type 1 diabetes mellitus with and without diabetic retinopathy. A total of 28 young patients (mean age, 22.86 ± 9.05 years) with type 1 diabetes, with (n = 18) and without (n = 10) retinopathy, and 17 age-matched healthy control subjects (mean age, 26.53 ± 2.43 years) underwent corneal confocal microscopy (CCM). We found significantly lower epithelial (P < 0.0001) and endothelial (P = 0.001) cell densities and higher keratocyte cell density (P = 0.024) in patients with type 1 diabetes compared to controls. Significantly lower corneal nerve fiber density (P = 0.004), nerve branch density (P = 0.004), total nerve branch density (P = 0.04), and nerve fiber length (P = 0.001), and greater nerve fiber width (P = 0.04) were observed in patients with type 1 diabetes compared to control subjects. Significantly lower epithelial (P < 0.001) and endothelial (P = 0.02) cell densities, nerve branch density (P = 0.02), and nerve fiber length (P = 0.04), and significantly higher keratocyte cell density (P = 0.02) were found in patients with type 1 diabetes without retinopathy compared to control subjects. Corneal confocal microscopy identifies corneal cellular and small nerve fiber pathology in young patients with type 1 diabetes without retinopathy, which increases in severity in those with retinopathy. Corneal confocal microscopy appears to have considerable use as an imaging biomarker for early subclinical pathology in young patients with type 1 diabetes mellitus.